(untitled) (Al-Academy, 2018)
The cinematographer mediates through the means of cinema and television a set of elements complementing each other in the light of developments in various sciences, culture and arts for the purpose of conveying the meaning to the recipient and achieve aesthetic taste. Despite the diversity of cinematographic media with its multiple forms, The researcher started from the principle of definition and knowledge of a technical phenomenon that emerged in the cinematographic medium through the treatment of dramatic events through the solutions of the exit line depends on the narrative of events in one place contributes to attract Mam spectator since this interesting phenomenon in the mediator, there .van question arises the adoption of that vision and the role played by component location and wizards through his directorial solutions techniques